Al-Asmaa Alhusna (the finest names) and the Opinion of Imam Ibn al-Banna - may God have Mercy on him - about them (Islamic Sciences Journal, 2023)
This research is entitled: (The finest Names and the opinion of Imam Ibn al-Bana’ - may God have mercy on him) and it included four topics that we dealt with in the first topic: Defining the best Names, their number and enumeration, and in the second topic: his views on the Most Beautiful Names that indicate innovation and invention, and we discussed in the third topic To: His views on the Most Beautiful Names that indicate proof of measure. As far as the fourth topic is concerned, we have devoted it to: His views on the Most Beautiful Names that indicate integrity and perfection, and the denial of analogy. We concluded with a conclusion that included the most important results that we reached in this research, and we followed it with the sources and references that we returned to in the research.